WACANA PEMILIHAN PUTERI INDONESIA: PENOLAKAN DAN PEMBELAAN TANGGAPAN WARGANET - Rahmatika, Laily; Laila, Malikatul; Wahyudi, Agus Budi (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
Social media are online features to get information and to express the positive and negative response for warganet. The case of the Election of Miss Indonesia 2020 is the form of rejection and defense responses. This study aims to describe the variatios of negative and positive sense warganet response in the Election of Miss Indonesia 2020 which mispronounced Pancasila. There are two variation of data: First, 53 forms of negative warganet responses. Second, 45 forms of positive responses. Data sources are 98 warganet responses on instagram.  Data were collected through reading and taking note. Theoretical triangulation is used to validate the data.  The analysis method uses distributional and referential identity and pragmatics. The results show the form of rejection and defense responses. First, negative sense responses as warganet’s rejection. Second, positive sense responses as warganet’s defense.